Use of Metarhizium anisopliae Chitinase Genes for Genotyping and Virulence Characterization. - Niassy, Saliou; Subramanian, Sevgan; Ekesi, Sunday; Bargul, Joel L; Villinger, Jandouwe; Maniania, Nguya K (BioMed Research International, 2013)
Virulence is the primary factor used for selection of entomopathogenic fungi (EPF) for development as biopesticides. To understand the genetic mechanisms underlying differences in virulence of fungal isolates on various arthropod pests, we compared the chitinase genes, chi2 and chi4, of 8 isolates of Metarhizium anisopliae. The clustering of the isolates showed various groups depending on their virulence. However, the analysis of their chitinase DNA sequences chi2 and chi4 did not reveal major divergences. Although their protein translates have been implicated in fungal virulence, the predicted protein structure of chi2 was identical for all isolates. Despite the critical role of chitin digestion in fungal infection, we conclude that chi2 and chi4 genes cannot serve as molecular markers to characterize observed variations in virulence among M. anisopliae isolates as previously suggested. Nevertheless, processes controlling the efficient upregulation of chitinase expression might be responsible for different virulence characteristics. Further studies using comparative "in vitro" chitin digestion techniques would be more appropriate to compare the quality and the quantity of chitinase production between fungal isolates.